Frequency of Hepatitis B and Hepatitis C in Psoriatic Patients (Medical Forum Monthly, 2024)
Objective: To determine the frequency of hepatitis B and hepatitis C in psoriatic patients.Study Design: Prospective cross-sectional studyPlace and Duration of Study: This study was conducted at the Dermatology Department of a Tertiary Health Care Facility, Dow University of Health Sciences& Civil Hospital Karachi from January 2014 to December 2014.Materials and Methods: Irrespective of age and sex, a total of 47 patients with diagnosis of psoriasis and psoriatic arthritis were enrolled for this study.Results: Out of 47 eligible subjects, 89.4 % were male. Most of the patients (36 %) had a body involvement of 25- 50 % and the commonest type of psoriasis was plaque type. On further analysis, 8 % of the subjects were found to be positive for HBsAg on ICT method, but only 6.4 % confirmed positive on CMI techniques. Anti HCV Antibody reported positive in 10.6 % of the patients on ICT methods and the same results confirmed on CMI techniques.Conclusion: The number of psoriatic patients suffering from hepatitis B & C virus is not very much significant but should be considered. Once it is positive, then the treatment options are totally different.